Governing indigenous recreation at a distance: a critical analysis of an after school active health intervention. Issue 2 (12th February 2018) - Norman, Moss E.; Petherick, LeAnne; Garcia, Eric; Giesbrecht, Gordon; Duhamel, Todd
ABSTRACT: Within the Canadian context, the physical activity levels of children and youth in the after school time period has become a source of public health concern. We argue that this concern is informed by broader public health crises, in particular the 'global obesity epidemic' and the closely related 'global pandemic of physical inactivity', and that these so-called 'crises' operate as part of a discursive regime that serves to justify after school interventions aimed at increasing the physical activity practices of children and youth. Although the objectives of such interventions are seemingly well intentioned, we suggest that such interventions nonetheless harbor difficult to discern, but potentially pernicious consequences, for the communities in which they are implemented. We focus our attention on the place-specific effects of one Public Health Agency of Canada-funded after school physical activity intervention – After the School Bell Rings (ASBR) – that was implemented in the mostly Indigenous, northern community of Placid, Manitoba. Based on a critical analysis of the ASBR program itself, along with interviews and focus groups with children, parents and recreation providers ( n  = 10) from the community of Placid, we contend that the ASBR serves to govern Indigenous recreation at a distance. We argue that when implemented in the place-specific context of Placid, the ASBR functions as part of a broader governmental assemblage composed of loosely connected discourses, institutions, socio-structural conditions and individuals that, when assembled, ultimately serve to govern geographically and culturally distinct communities. We conclude by suggesting that the objectives of broad-based health interventions, such as the goal of increasing after school physical activity levels, should not be universally implemented across diverse locales, but need to account for the diverse, place-specific priorities and needs of the communities into which they are implemented.